Arquitetura de interface: análise de formas de organização da informação na interação entre pessoas e códigos - Prado, Renato Silva de Almeida (2006)
Two important facts are observed in the communicational processes in the last two decades. The first one is the mass use of the computers on a global scale digital support and the second one is the connection between them the net. Both facts were accompanied by significant changes in the interface between man and machine. The wide spread of the computer had its beginning connected with the adoption of the graphic interface rather than the command-line interface and also the assimilation of the mouse. The growth of the net internet also was influenced by an interface change, when Mosaic appeared in 1993. The early internet, basically formed by textual information starts to work in a multimedia way, with sound and image along with the text. This project intends to analyze the unfolding of these two facts, by means of reading and analysis of some aspects of the digital culture and net culture, as well as to raise concepts and characteristics pertinent to these contexts for the development of new interfaces that can represent a new step or progress in an interaction form. More than ten years have passed and the signs of these changes are more and more evident and intricate in our social and cultural daily life. The discussion about the needs for new interfaces is already significant as Steven Johnson, Richard Grusin, Jay David Bolter, Lev Manovich, Giselle Beiguelman and Peter Weibel put it. This work is based greatly, besides the authors above, in the points of view of Alexander Galloway and Howard Rheingold. The relevance of this study is more evident as the digital interfaces are more and more present in so many social layers and activities, but now they have their capacity questioned. Today s graphic interface still has some of their characteristics attributed in the 70 s, and developed to work basically with a quantity of information restricted to one computer. At the same time it accesses and manipulates a much bigger quantity of information, come from and distributed to billions of computers